WOMEN IN REPRODUCTIVE SCIENCE: Discovering science and the ovary: a career of joy. Issue 6 (December 2019) - Richards, JoAnne S
Abstract : My career has been about discovering science and learning the joys of the discovery process itself. It has been a challenging but rewarding process filled with many exciting moments and wonderful colleagues and students. Although I went to college to become a French major, I ultimately stumbled into research while pursuing a Masters Degree in teaching. Thus, my research career began in graduate school where I was studying NAD kinase in the ovary as a possible regulator of steroidogenesis, a big issue in the late 1960s. After a short excursion of teaching in North Dakota, I became a postdoctoral fellow at the University of Michigan, where radio-immuno assays and radio receptor assays had just come on the scene and were transforming endocrinology from laborious bioassays to quantitative science and of course these assays related to the ovary. From there I went to Baylor College of Medicine, a mecca of molecular biology, cloning genes and generating mouse models. It has been a fascinating and joyous journey.